Throne of Glass: Throne of Glass Series # 1 - Maas, Sarah J. (New York : Bloomsbury, 2012)
After she has served a year of hard labor in the salt mines of Endovier for her crimes, Crown Prince Dorian offers eighteen-year-old assassin Celaena Sardothien her freedom on the condition that she act as his champion in a competition to find a new royal assassin.
After she has served a year of hard labor in the salt mines of Endovier for her crimes, Crown Prince Dorian offers assassin Celaena Sardothien her freedom on the condition that she act as his champion in a competition to find a new royal assassin.
Keywords: Fantasy; Assassins -- Fiction; Princes -- Fiction; Courts and courtiers -- Fiction; Prisoners -- Fiction; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Love & Romance; Assassins -- Fiction; Princes -- Fiction; Courts and courtiers -- Fiction; Prisoners -- Fiction; Fantasy fiction